Strategi Meningkatkan Perceived Value Melalui Peningkatan Product Qualty untuk Mendorong Kepuasan Pelanggan dan Word of Mouth - Wiwin Fitriani; Puji Astuti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Indonesian society tends to prioritize the use of skincare over makeup, making it essential for businesses to be responsive and intelligent in designing marketing programs to attract consumers and create repurchase intention. This study aims to explore the relationship between Perceived Quality, which can enhance Repurchase Intention, and Word of Mouth, either directly or through perceived value and satisfaction. The research method uses purposive sampling with the following criteria: Sociolla consumers in the Jabodetabek area, aged 17-45 years, who have purchased skincare from Sociolla at least twice in the last three months. Data analysis employs Structural Equation Modeling (SEM) with Lisrel, using a sample of 240 respondents. The research findings prove that Perceived Quality positively affects Perceived Value, Satisfaction, Repurchase Intention, and Word of Mouth. However, Perceived Value positively influences Satisfaction, but Perceived Value and Satisfaction do not affect Repurchase Intention; instead, they influence Word of Mouth. Perceived Value and Satisfaction do not mediate the relationship between Perceived Quality and Repurchase Intention, but they mediate the relationship between Perceived Quality and Word of Mouth. Furthermore, Satisfaction does not mediate the relationship between Perceived Value and Repurchase Intention or Perceived Value and Word of Mouth. Future research is expected to expand the scope of location, respondents, and objects. The contribution of this research to creating Repurchase Intention and Word of Mouth requires improving product quality, product value, and customer satisfaction.